Studi kasus implementasi program pencegahan dan pengendalian infeksi saluran pernafasan akut pneumonia pada kegiatan penemuan kasus pneumonia balita di puskesmas - Sri Maya Guswahyuni; Djauhar Ismail; Sri Mujianto (Berita Kedokteran Masyarakat (BKM), 2019)
Case study of implementation pneumonia prevention and control program: case finding on the children under five years old at puskesmas by IMCI approachPurpose: This study aims to evaluate the Prevention and Control program for ARI Pneumonia through pneumonia case finding activities for toddlers in Kerinci District health centers. Methods: This study is evaluation research used qualitative methods with a case study program implementation plan, located at Sungai Tutung Health Center, Kerinci District, Jambi Province, using a logic model program theory with evaluation steps referring to the program evaluation framework recommended by the Center For Disease Control and Prevention. Interviews were conducted on 15 informants including triangular informants. Key informants are primary health care providers who are associated with ARI pneumonia. Results: The results of the study, the case-findings of pneumonia cases passively was not optimal because it did not meet the standard of cough testing and IMCI approach. Lack of knowledge, low motivation, and weakness, monitoring, and evaluation from the health office are obstacles to ARI pneumonia programs in addition to budget or funding limitations. Conclusions: The recommendation is to allocate a budget for the P2 ISPA program, facilitate the improvement of knowledge and skills for P2 ISPA Primary health care officers, establish cross-program and cross-sector cooperation in expanding the reach of P2 ISPA program in the finding of pneumonia cases in toddlers in health centers.